Trichopria anastrephae: A Promising Neotropical-Native Parasitoid for Drosophila suzukii Control - Buonocore Biancheri, María Josefina (2024)
Drosophila suzukii (Matsumura) is an invasive pest mainly affecting berry and stone fruit crops worldwide. In Argentina, it inhabits fruit-growing regions. An eco-friendly management strategy involves biological control by using resident natural enemies, such as the Neotropical-native pupal parasitoid Trichopria anastrephae Lima (Ta). The study compared the host-killing capacity and the offspring reproductive success of two Ta lineages on the puparia of both D. suzukii (Ds) and D. melanogaster (Dm) in no-choice and choice tests under laboratory conditions. The host preference and host-switching behaviors were also assessed. One parasitoid lineage was reared on Ds (TaDs), and the second on Dm (TaDm). In no-choice tests, both Ta lineages performed similarly on both hosts regarding the percentage of killed hosts and parasitoid offspring survival. The host-killing ability of TaDm was only significantly lower when Ds was offered as a host, relative to Dm. In choice tests, Ta attacked mainly Ds at a 4–9 times Ds to Dm ratio, but at a 1.5–2 times Ds to Dm ratio, the host-killing ability was similar between both drosophilids. At an equal host ratio or higher Dm ratios, Ta preferred the native host. However, it was determined that Ta has the potential to parasitize the recently-introduced pest.